Earthquake threat to municipalities and settlements in Slovenia - Orožen Adamič, Milan (Geografski zbornik, 1996)
Since January 1, 1995, Slovenia has had 147 municipalities and almost 6.000 settlements. Using the Geographical Information System, we combined a layer with seismic zones, a layer with municipal borders, and a layer with centroids (coordinates) of settlements. For every municipality and settlement in Slovenia we first determined a partial assessment of the earthquake threat to municipalities relative to surfaces and population, a partial assessment of the earthquake threat to settlements relative to population, relative to the active population, that is, to the number of work places, and relative to the age of housing. We then obtained an aggregate assessment of the eartquake threat to settlements relative to population and the age of housing.
Keywords: naselja; ogroženost; potresi; prebivalstvo; Slovenia; Slovenija